(untitled) (INTERNATIONAL CONFERENCE ON MODERN DEVELOPMENT OF PEDAGOGY AND LINGUISTICS, 2025)
This study looks at how real-time AI feedback helps ESL students speak more fluently. During six weeks, one group used AI speaking apps, and another group used traditional practice. The students who used AI improved their fluency and pronunciation more than the other group. The results show that AI feedback can help learners speak more confidently and correctly. It also helps them learn faster and stay motivated.